La representación política de las Cortes de Castilla durante los Austrias - Álvarez García, Héctor (Revista de Derecho de la UNED (RDUNED), 2018)
El trabajo tiene por objeto analizar la naturaleza representativa de las Cortes de Castilla durante los siglos xvi y xvii. Sus orígenes se encuentran en los concilios de la monarquía visigoda y en las Cortes de León de 1188, a las que concurrieron por primera vez en la historia política europea representantes del tercer estado. Asimismo, estudiaremos la relación jurídico-política que ligaba a los procuradores de Cortes con sus ciudades (mandato imperativo) y la dialéctica Cortes del Reino versus Cortes de las Ciudades (mandato representativo vs mandato imperativo), que tuvo lugar durante el reinado de la dinastía Habsburgo en España. The work aims to analyze the representative nature of the Parliament of Castile during the sixteenth and seventeenth centuries. Its origins are in the councils of visigothic monarchy and in the Parliament of Leon of 1188, to which representatives of the third state participated for the first time in European political history. Likewise, we will study the juridical-political relationship that linked Parliament´s representatives with their cities (imperative mandate) and the dialectic Parliament of Kingdom versus Parliament of Cities (representative mandate vs. imperative mandate), which took place during the dinasty Habsburg´s reign in Spain.